Spam filtering algorithm based on geographic E-mail path analysis - ZHANG Ni1; JIANG Yu2; FANG Bin-xing1; LI Guo1 (Tongxin xuebao)
A geographic E-mail path based algorithm called GEPA（geographic E-mail path analysis） was proposed to al-low network administrators to cut off spam traffic on E-mail delivery.The algorithm first extracted route information to build E-mail path subset,and then uesed an effective method mapping IP addresses or domain names of nodes in an E-mail path into geographic information.Further,the algorithm detected spam by their geographic information deviation,using E-mail traffics from a link of backbone border router in China,which crosses the country boundary of China,the performance of GEPA algorithm is evaluated.The experimental results indicated that a 13.9% reduction of E-mail can be achieved with method.The results also showed GEPA was effective and practical which can be implemented in a mas-sive traffic environment handling over millions of mails every day with small memory consumption.